Impact of gluconic fermentation of strawberry using acetic acid bacteria on amino acids and biogenic amines profile. (1st July 2015) - Ordóñez, J.L.; Sainz, F.; Callejón, R.M.; Troncoso, A.M.; Torija, M.J.; García-Parrilla, M.C.
Highlights: Biogenic amines were not detected in substrates and gluconic fermented products. Gluconobacter japonicus presented the highest consumption of amino acids. LDA could group the samples from gluconic acid fermented according to the strain. Gln, Ala and Tryp showed a significant decrease during gluconic fermentation. Arg, GABA and Pro increased significantly during fermentation. Abstract: This paper studies the amino acid profile of beverages obtained through the fermentation of strawberry purée by a surface culture using three strains belonging to different acetic acid bacteria species (one of Gluconobacter japonicus, one of Gluconobacter oxydans and one of Acetobacter malorum ). An HPLC–UV method involving diethyl ethoxymethylenemalonate (DEEMM) was adapted and validated. From the entire set of 21 amino acids, multiple linear regressions showed that glutamine, alanine, arginine, tryptophan, GABA and proline were significantly related to the fermentation process. Furthermore, linear discriminant analysis classified 100% of the samples correctly in accordance with the microorganism involved. G. japonicus consumed glucose most quickly and achieved the greatest decrease in amino acid concentration. None of the 8 biogenic amines were detected in the final products, which could serve as a safety guarantee for these strawberry gluconic fermentation beverages, in this regard.